Effects of the COVID-19 pandemic on the physical activity and screen time habits of children aged 11–13 years in Sweden - Berggren, Sara; Almquist-Tangen, Gerd; Wolfbrandt, Olivia; Roswall, Josefine (Frontiers in Public Health, 2023)
Introduction: Physical activity (PA), exercise, sedentary behavior and screen time are lifestyle factors that have been shown to significantly impact child health in different ways. These lifestyle factors were affected to different degrees by global restrictions during the COVID-19 pandemic. We investigated PA and screen time in a cohort of Swedish children in both 2019 and 2021, before and during the pandemic. Method: Adolescents born in 2008 in Halland, Sweden, and included in a previous longitudinal birth cohort study were invited to take part in follow-up questionnaires about PA, screen time and COVID-19. A total of 1041 children aged 11 (in 2019) and 13 years (in 2021) replied and 777 of them answered on both occasions. Results: Most children (42.1%) reported that their leisure time PA was unchanged from 2019 to 2021. Compared to unchanged PA33.9% exercised more often (p=0.011) and 23.9% exercised less (p<0.001), both differences statistically significant. Roughly, 43.2% of boys and 34.9% of girls in 2021 exercised so that they became breathless or broke a sweat at least 4 times a week not counting physical education in school, corresponding figures for 2019 were 38.2% for boys and 35.2% for girls. The majority of children were able to continue attending leisure time sports clubs during the pandemic, but participation decreased from 88.3% to 76.3% from 11 to 13 years of age. Most reported that sports club routines changed during the pandemic, but only 40.9% reported fewer practice opportunities. Attending a sports club gave greater protection against loss of PA during the pandemic than not belonging to one (41.0% vs 23.2%, p< 0.001). The majority (71.1%) of children spent more time on screens in 2021 than 2019, with a mean increase of 9.4 hours (95% CI 8.6 to 10.2 hours) from 20.7 to 30.1 hours per week (p<0.001) during the study. Conclusions: Swedish children largely maintained their levels of PA during the pandemic at 13 years of age and these were possibly safeguarded by the comparably mild pandemic restrictions in Sweden in 2021. However, they did increase their screen time between 11 and 13 years of age.